Pengendalian Parameter Persediaan Genuine Spare Part Mobil Wuling Menggunakan Pendekatan FMEA (Failure Mode and Effect Analysis) - Laia, David Kharun; Herlina, Herlina (Fakultas Teknik UMRI, 2024)
PT XWZ is a service company engaged in the automotive sector, which serves the stages of unit sales to service car vehicles (after sales service) for the Wuling car brand. In improving the vehicle service or maintenance process, it is necessary to have an optimal availability of spare parts. From the inventory data in the warehouse, the majority of spare parts stored in the warehouse are classified as slow moving parts. By conducting an ABC and FMEA approach, it is expected to be able to increase the reliability of maintenance needs so as to increase inventory according to the criticality value of spare parts. In this research, 19 spare parts items were found to be classified as critical or high risk items.